Is Early Appropriate Care of axial and femoral fractures appropriate in multiply-injured elderly trauma patients?. Issue 1 (December 2016) - Reich, M.; Dolenc, A.; Moore, T.; Vallier, H.
Abstract Background Previous work established resuscitation parameters that minimize complications with early fracture management. This Early Appropriate Care (EAC) protocol was applied to patients with advanced age to determine if they require unique parameters to mitigate complications. Methods Between October 2010 and March 2013, 376 consecutive skeletally mature patients with unstable fractures of the pelvis, acetabulum, thoracolumbar spine, and/or proximal or diaphyseal femur fractures were treated at a level I trauma center and were prospectively studied. Patients aged ≤30 years (n = 114), 30 to 60 years (n = 184), and ≥60 years (n = 37) with Injury Severity Scores (ISS) ≥16 and unstable fractures of the pelvis, acetabulum, spine, and/or diaphyseal femur were treated within 36 h, provided they showed evidence of adequate resuscitation. ISS, Glasgow Coma Scale (GCS), and American Society of Anesthesiologists (ASA) classification were determined. Lactate, pH, and base excess (BE) were measured at 8-h intervals. Complications included pneumonia, pulmonary embolism (PE), acute renal failure, acute respiratory distress syndrome (ARDS), multiple organ failure (MOF), deep vein thrombosis, infection, sepsis, and death. Results Patients ≤30 years old (y/o) were more likely to sustain gunshot wounds (p = 0.039), while those ≥60 y/o were more likely to fall from a height (p = 0.002). Complications occurred at similar rates for patients ≤30 y/o, 30 to 60 y/o, and ≥60 y/o. There were no differences in lactate, pH, or BE at the time of surgery. For patients ≤30 y/o, there were increased overall complications if pH was <7.30 (p = 0.042) or BE <−6.0 (p = 0.049); patients ≥60 y/o demonstrated more sepsis if BE was <−6.0 (p = 0.046). Conclusions EAC aims to definitively manage axial and femoral shaft fractures once patients have been adequately resuscitated to minimize complications. EAC is associated with comparable complication rates in young and elderly patients. Further study is warranted with a larger sample to further validate EAC in elderly patients. Level of evidence: level II prospective, comparative study.